District Administration and Service Delivery: Gaps and Way Forward - Malik, Mudassir Riaz (Journal of Pakistan Administration, 2023)
A country’s governance is a function the effectiveness of its public service delivery systems. Pakistan still ranks low in terms of its 32 percentile ranking in the Government Effectiveness Index (part of World Bank’s Worldwide Governance Indicators 2020). Even though the province of Punjab has taken several initiatives to improve service delivery at the district level, citizens in general are not satisfied with services at public facilities. This paper explores the association of accessibility to services, quality of services and public sector integrity through a logit model with overall satisfaction of citizens towards services. The study employs a quantitative approach to examine the association and collects data through survey of citizens by means of a structured and close-ended questionnaire administered at selected public facilities in Lahore and Faisalabad. The study also conducts a gap analysis between citizens’ perceptions of service delivery and understanding of public administration. The district administration structure for service delivery in Punjab is one of a hybrid nature with comprehensive framework of laws and policies including Local Government Act 2019 and Civil Administration Act 2017 placing Deputy Commissioner at an important position for coordinating public facilities as well as supervising service delivery systems. Moreover, the data collected shows that the majority of respondents are young males hailing from urban areas, self-employed and educated. Even though 70 percent of the respondents expressed satisfaction with the services received, interestingly 38 percent of them approached the public facility with some reference - an indication of their lack of trust in “normal” service delivery. The study finds that quality of services and public sector integrity significantly explain citizens’ overall satisfaction towards effective service delivery in spite of the fact that accessibility and leadership role are not found predictive of the same. Similarly, the widest gap between citizens’ satisfaction with service delivery and administrators’ perception of these services lies in public sector integrity. The study concludes that focus areas of public administrators for improving service delivery include enhanced responsiveness and quality of services, digitalization, and transparency. The study recommends that dedicated desks with staff skilled in dealing with citizens, automation of services and effective complaint management systems can help improve citizens’ perceptions towards effective service delivery.
Keywords: district administration; public service; quality of services